The Pedagogical Mediation of a Developmental Learner Corpus for Classroom-Based Language Instruction - Julie A. Belz; Nina Vyatkina (Language Learning and Technology, 2008)
Although corpora have been used in language teaching for some time, few empirical studies explore their impact on learning outcomes. We provide a microgenetic account of learners’ responses to corpus-driven instructional units for German modal particles and pronominal da-compounds. The units are based on developmental corpus data produced by native speakers during interactions with the very learners for whom the units are designed. Thus, we address the issue of authentication in corpus-driven language pedagogy. Finally, we illustrate how an ethnographically supplemented developmental learner corpus may contribute to second language acquisition research via dense documentation of micro-changes in learners’ language use over time.